Dynamic Cure Kinetics and Physical-Mechanical Properties of PEG/Nanosilica/Epoxy Composites - Haleh Nowruzi Varzeghani; Iraj Amiri Amraei; Seyed Rasoul Mousavi (International Journal of Polymer Science)
This study investigated the effect of polyethylene glycol (PEG) and nanosilica (NS) on the physical-mechanical properties and cure kinetics of diglycidyl ether of bisphenol-A-based epoxy (DGEBA-based EP) resin. For this purpose, tensile and viscometry tests, dynamic mechanical thermal analysis (DMTA), and differential scanning calorimetry (DSC) were carried out under dynamic conditions. The results showed that adding NS and PEG enhances the maximum cure temperature as well as the heat of cure reaction (ΔH) in EP-NS, while it decreases in EP-PEG and EP-PEG-NS. The cure kinetic parameters of EP-PEG-NS were calculated by Kissinger, Ozawa, and KSA methods and compared with each other. The Ea calculated from the Kissinger method (96.82 kJ/mol) was found to be lower than that of the Ozawa method (98.69 kJ/mol). Also, according to the KAS method, the apparent Ea was approximately constant within the 10-90% conversion range. Tensile strength and modulus increased by adding NS, while tensile strength diminished slightly by adding PEG to EP-NS. The glass transition temperature (Tg) was calculated using DMTA which was increased and decreased by the addition of NS and PEG, respectively. The results of the viscometry test showed that the viscosity increased with the presence of both PEG and NS and it prevented the deposition of solid particles.